Digital education resource data management plan template [draft] - Brennan, Niamh; RIOSE (Trinity College Dublin, The University of Dublin, 2020)
This template is intended for creating a digital education resource data management plan. It is based on the Science Europe Research Data Management Plan template and adapted from the NWO Data Management Plan template. This template helps digital education course developers and providers to apply the FAIR data management principles to their digital education resources.
Keywords: Instructional design, principles; data management, educational; data management plan